Polymers for the treatment of Alzheimer’s disease - Zhu, Yunfeng; Xu, Haibin; Yu, Chaoyan; Jiang, Wenting; Hou, Xiaowen; Ma, Mingyue; Wu, Ji (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is one of the most common diseases of the central nervous system in the middle-aged and elderly population. It is a neurodegenerative disorder, and its main clinical symptoms include the loss of established memories, a decline in learning capacity, and the buildup of β-amyloid peptides. The disease is often accompanied by neurodegenerative changes and the formation of neurofibrillary tangles. However, the number of drugs available for the clinical treatment of AD remains limited. Currently, existing medications are not effective in completely curing the disease or stopping its progression. Due to their excellent biocompatibility and biodegradability, polymers have been widely used as drug delivery carriers in various fields including cancer therapy and wound healing. The use of polymers enables targeted drug delivery and prolonged release profiles. In recent years, researchers have made significant progress in utilizing polymers such as polyethylene glycol, poly (lactic-co-glycolic acid) (PLGA), and chitosan (CS) to deliver drugs and blood-brain barrier receptor ligands for the treatment of AD. Moreover, many polymers with inherent therapeutic properties have been developed, including the already marketed GV-971 as well as experimental polymers such as PLGA and CS oligosaccharide. This review summarizes the applications of polymers in AD treatment over the past few years and highlights their current limitations to help researchers better understand current advancements in polymer development and identify future research directions.